2002
DOI: 10.1080/0268396022000018409
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Comparison of Electronic Commerce Adoption in Large and Small Enterprises

Abstract: This study compares the reasons why small and large companies are adopting electronic commerce (ecommerce) and compares the bene ts realized from the adoption of e-commerce by these two groups of companies. Two surveys that were undertaken contemporaneously on the use of e-commerce by small and large companies in the UK were used as the empirical basis for this study. The study found that the use of e-commerce for responding to competitors, providing enhanced customer services and improving relations with supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
85
1
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(112 citation statements)
references
References 48 publications
7
85
1
6
Order By: Relevance
“…Previous works pointed out that e-commerce is a solution that would steer firms to a better financial performance and increased competitiveness and efficiency in operations. Despite these perceived improvements, managers of SMEs are still sceptical towards the adoption of SMEs due to their respective resource and technological limitations (Migiro 2006, Daniel andGrimshaw 2002). Based on surveys in several countries such as Kenya, SMEs have limited access to the Internet, market, finance, and the latest technologies (Maswera et al 2008).…”
Section: Roger's Theorymentioning
confidence: 99%
“…Previous works pointed out that e-commerce is a solution that would steer firms to a better financial performance and increased competitiveness and efficiency in operations. Despite these perceived improvements, managers of SMEs are still sceptical towards the adoption of SMEs due to their respective resource and technological limitations (Migiro 2006, Daniel andGrimshaw 2002). Based on surveys in several countries such as Kenya, SMEs have limited access to the Internet, market, finance, and the latest technologies (Maswera et al 2008).…”
Section: Roger's Theorymentioning
confidence: 99%
“…• La internacionalización de la empresa y la pertenencia de colaboraciones externas puede incrementar la probabilidad de incursionar en el comercio electróni-co (Daniel y Grimshaw, 2002;Wagner et al, 2003).…”
Section: Marco Teóricounclassified
“…The following is a discussion of some studies on the level of adoption by SMEs. Daniel and Grimshaw (2002) studied the adoption of E-commerce by UK SMEs from a stage perspective. They found that there are four stages or steps through which firms passed during the adoption of e-commerce namely; developers, communicators, web presence and translators.…”
Section: Internet Adoption By Smesmentioning
confidence: 99%